2008
DOI: 10.1146/annurev.arplant.59.032607.092752
|View full text |Cite
|
Sign up to set email alerts
|

Flooding Stress: Acclimations and Genetic Diversity

Abstract: Flooding is an environmental stress for many natural and man-made ecosystems worldwide. Genetic diversity in the plant response to flooding includes alterations in architecture, metabolism, and elongation growth associated with a low O(2) escape strategy and an antithetical quiescence scheme that allows endurance of prolonged submergence. Flooding is frequently accompanied with a reduction of cellular O(2) content that is particularly severe when photosynthesis is limited or absent. This necessitates the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

27
1,195
1
30

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,407 publications
(1,253 citation statements)
references
References 157 publications
27
1,195
1
30
Order By: Relevance
“…Amino acid metabolism is affected by oxygen and energy shortage, however, the role of accumulated amino acids under low oxygen stress is still elusive (Bailey-Serres and Voesenek 2008;Bailey-Serres et al 2012). An interesting comparison of protein and metabolite profiling in response to low oxygen stress between rice and wheat coleoptiles showed in rice coleoptiles, but not in wheat coleoptiles increased abundance of a set of enzymes involved in alanine, serine and glycine biosynthesis with the accumulation of these amino acids in rice coleoptiles (Shingaki-Wells et al 2011).…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
See 4 more Smart Citations
“…Amino acid metabolism is affected by oxygen and energy shortage, however, the role of accumulated amino acids under low oxygen stress is still elusive (Bailey-Serres and Voesenek 2008;Bailey-Serres et al 2012). An interesting comparison of protein and metabolite profiling in response to low oxygen stress between rice and wheat coleoptiles showed in rice coleoptiles, but not in wheat coleoptiles increased abundance of a set of enzymes involved in alanine, serine and glycine biosynthesis with the accumulation of these amino acids in rice coleoptiles (Shingaki-Wells et al 2011).…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…NR activity is increased by virtue of its low pH optimum (Stoimenova et al 2007). Phosphorylation of GDH for decreasing its activity under hypoxic condition is hypothesized based on the posttranslational regulation of this enzyme in crayfish Orconectes virilis (Dawson and Storey 2012) goes beyond alanine accumulation (Bailey-Serres and Voesenek 2008;Bailey-Serres et al 2012). It has been suggested that the adaptive response of amino acid metabolism to hypoxic stress consists of a concerted modulation of the flux of organic N going through glutamate and alanine (Limami et al 2008).…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
See 3 more Smart Citations